Systemic immunostimulation induces glucocorticoid-mediated thymic involution succeeded by rebound hyperplasia which is impaired in aged recipients - Collins, Craig P.; Khuat, Lam T.; Sckisel, Gail D.; Vick, Logan V.; Minnar, Christine M.; Dunai, Cordelia; Le, Catherine T.; Curti, Brendan D.; Crittenden, Marka; Merleev, Alexander; Sheng, Michael; Chao, Nelson J.; et al. (Frontiers in Immunology, 2024)
The thymus is the central organ involved with T-cell development and the production of naïve T cells. During normal aging, the thymus undergoes marked involution, reducing naïve T-cell output and resulting in a predominance of long-lived memory T cells in the periphery. Using both mouse and human systems, the thymic effects of systemic immunostimulatory regimens, such as high dose IL-2 (HD IL-2) with or without agonistic anti-CD40 mAbs and acute primary viral infection, were investigated. These regimens produced a marked acute thymic involution in mice, which correlated with elevated serum glucocorticoid levels and a diminishment of naïve T cells in the periphery. This effect was transient and followed with a rapid thymic "rebound" effect, in which an even greater quantity of thymocytes was observed compared to controls. Similar results were observed in humans, as patients receiving HD IL-2 treatment for cancer demonstrated significantly increased cortisol levels, accompanied by decreased peripheral blood naïve T cells and reduced T-cell receptor excision circles (TRECs), a marker indicative of recent thymic emigrants. Mice adrenalectomized prior to receiving immunotherapy or viral infection demonstrated protection from this glucocorticoid-mediated thymic involution, despite experiencing a substantially higher inflammatory cytokine response and increased immunopathology. Investigation into the effects of immunostimulation on middle aged (7-12 months) and advance aged (22-24 months) mice, which had already undergone significant thymic involution and had a diminished naïve T cell population in the periphery at baseline, revealed that even further involution was incurred.Thymic rebound hyperplasia, however, only occurred in young and middle-aged recipients, while advance aged not only lacked this rebound hyperplasia, but were entirely absent of any indication of thymic restoration. This coincided with prolonged deficits in naïve T cell numbers in advanced aged recipients, further skewing the already memory dominant T cell pool. These results demonstrate that, in both mice and humans, systemic immunostimulatory cancer therapies, as well as immune challenges like subacute viral infections, have the potential to induce profound, but transient, glucocorticoid-mediated thymic involution and substantially reduced thymic output, resulting in the reduction of peripheral naive T cells.